Breastfeeding Best Practices in Higher Education - Vancour, Michele L.; Griswold, Michele K. (Hale Publishing, 2014)
Keywords: Breastfeeding promotion; College environment; United States; dept.hhs; faculty_collection

A research update on correlates of heavy episodic drinking among undergraduate college students. - Montauti, Sara; Bulmer, Sandra Minor (American Journal of Health Education, 2014)
Despite prevention efforts of colleges and universities across the nation, there have been no substantial decreases in heavy episodic drinking among undergraduates over the past 2 decades.This study provides an update on correlates of heavy episodic drinking for a recent cohort of undergraduate college students.A cross-sectional survey design was utilized. Participants were randomly selected undergraduate students from a public 4-year university located in the Northeast.Heavy episodic drinking was associated with male gender, white race, having a family history of drug or alcohol abuse, smoking cigarettes, and using marijuana. Age, athlete status, completion of an alcohol education program, condom use, depression, anxiety, and financial stress were not associated. After controlling for gender and race, marijuana use and smoking cigarettes were found to increase predictability of heavy episodic drinking.Rates of heavy episodic drinking remain high but correlates may be shifting for this cohort of college students. Opportunities to address heavy episodic drinking concurrently with cigarette smoking and marijuana use should be explored.Qualitative research methods are needed to gain insight into reasons for heavy episodic drinking; information that could inform the creation of more effective programming. © 2014 Copyright © SHAPE America.
Keywords: dept.hhs